Car driver asissted for blind spot detection system - Siti Khadijah, Mohamad (2012)
Car Driver Assisted for Blind Spot System is invented to observe the blind spot region and alert the driver automatically to ensure the driver safety on highway due to the driver inability to observe the blind spot area directly which had caused many accident occur. Eventually, the system is built from a combination of a circuit and programming software of microcontroller and ultrasonic sensor. In this project, 2 ultrasonic sensors will be put at the right side of a car because the risk of danger in the blind spot is higher at the driver side. The sensors will be put on the lateral side of the front and rear side of a car to check the incoming vehicle at the blind spot. The sensors will be activated at a certain speed and when both sensors detect a vehicle at the blind spot, a warning system will trigger. An indicator light or LED located at the side mirror will be used as visual warning system while a buzzer will be used as audio warning system which can be install inside the car. Hence, the system will help a driver to drive safely and prevent any fatal accident involving blind spot. As the result, the statistic for accident can be lower.